A rare case of solitary gallbladder metastasis from an early cutaneous melanoma - Emily Louise Doole (Wiley, 2021)
Abstract Solitary gallbladder metastasis from melanoma is a rare phenomenon, in this case manifesting as biliary symptoms during and following pregnancy. It is important to consider uncommon causes of biliary symptoms to aid in prompt diagnosis and treatment. This patient was successfully treated with laparoscopic cholecystectomy and adjuvant immunotherapy.